ChemInform Abstract: Copper‐Catalyzed Synthesis of Imidazol[1, 2‐α]pyridines Through Tandem Imine Formation‐Oxidative Cyclization under Ambient Air: One‐Step Synthesis of Zolimidine on a Gram‐Scale. Issue 45 (14th October 2013) - Bagdi, Avik Kumar; Rahman, Matiur; Santra, Sougata; Majee, Adinath; Hajra, Alakananda
Abstract The simple cyclization reaction of 2‐aminopyridines and ketones is tolerant to a wide range of functional groups.